The effectiveness of watermelon rind extracts waste (citrullus lanatus l.) in removing free radical in oral leukoplakia patients - Shafira N. Khaera; Ainiyyah F. Zaizafun; Andi N. Anisa; Acing H. Mude (Journal of Dentomaxillofacial Science, 2022)
Objective: Therefore, this study will reveal the effectiveness of watermelon rind extract waste in inhibiting free radicals in patients with oral leukoplakia. Material and Methods: The extraction method used is maceration. One hundred grams of watermelon rind powder (112 g) added 700 ml of 96% ethanol. Then soak for 3 days. The extract is filtered using a filter to separate the filtrate and its residue. After that solvent evaporation was carried out until the dried extract was obtained, then tested the antioxidant activity of the extract using DPPH free radical catcher. Results: Watermelon rind extract is classified as a powerful antioxidant because it has a ppm value ranging from 50-100 ppm. Conclusion: It can be proven that the watermelon rind which is more often disposed of can also be used, contains vitamin C and lycopene which can connect freely to patients with leukoplakia and can be used as a support therapy for surgical therapy as a cause of leukoplakia disease.